Physical Disease: A Crucial Research Area in the Context of Quality of Life and Mental Health - Paraskevi Theofilou (MDPI AG, 2023)
The medical literature defines a chronic physical disease as any organic disorder that lasts more than three months or that entails a period of hospitalization of more than of a month, which restricts an individual's daily abilities or behaviors and causes changes to their social functions [...]